LEARNING WRITING TEXT EXPLLANATION AND STUDY LEARNING STUDENTS VIII SMP ASSALAAM BANDUNG USING USINGTHINK METHOD OF PAIR AND SHARE - Deni Lastari; Yesi Meylani Meylani Kartiwi; Asep Kusnadi Permana (JLER (Journal of Language Education Research), 2018)
This research entitled "Explanation Writing Learning and Self-Reliance Learning of Junior High School Assalaam Bandung by Using Think Pair and Share Method In Grade VIII Junior High School Assalaam Bandung Academic Year 2017/2018 '' Based on the above title the problems are difficult to write explanatory text such as determining characteristics, structure, and linguistic. To find out whether or not the skills of writing explanatory text students SMP Assalaam Bandung learning using Think Pair and Share method is better than using a scientific method?. To know the skills of writing explanatory text of junior high school students Assalaam Bandung learning using Think Pair and Share method is better than that using scientific method. The Reseacher method used in this research is quasi experiment. The population in this study is students of class VIII SMP Assalaam Bandung with a sample of two classes totaling 62 students. Based on the research, the average value of the final test of the experimental class is 76.67 while the control class class gets the average of the final test score of 68,7. The results of this study showed that the results of student learning by using methods Think Pair and Share better than the lecture method on the subjects of writing explanatory text.